Oxidative stress-mediated hepatotoxicity in rats induced by ethanol extracts of different parts of Chloranthus serratus - Shuping Sun; Yang Wang; Yunyan Du; Qi Sun; Lijuan He; Enze Zhu; Jiarong Li (Taylor & Francis Group, 2020)
Context Chloranthus serratus (Thunb.) Roem. et Schult. (Chloranthaceae) is an herb widely used as a folk medicine treating inflammatory diseases, although it is toxic. Objective To investigate hepatotoxicity and related mechanisms induced by ethanol extracts of different parts of C. serratus in rats. Materials and methods Sprague Dawley rats were divided into control (Con), ethanol extract of roots (ER), stems (ES), and leaves (EL) groups, and acute oral toxicity studies were conducted. The rats received doses of 4.14, 3.20, and 1.16 g/kg/d extracts for 14 days, respectively. Liver index, liver function and oxidative stress biomarkers, liver pathology, ultrastructure, TNF-α, ICAM-1, and Nrf2/HO-1 proteins expression levels were determined. Results The LD50 of ER, ES, and EL were higher than 10.35, 8.05, and 2.90 g/kg/p.o., respectively. The liver indexes in the extract groups increased significantly. EL dramatically increased TP, GLB, AST, ALT, ALP, TBA, MDA, ICAM-1, and TNF-α levels (p < 0.01), and induced the most obvious pathological and ultrastructural changes. ES and EL obviously decreased the T-SOD, GSH, CAT, and CHOL levels. Nrf2 and HO-1 proteins expression was reduced significantly in ES (0.77 ± 0.06, 2.33 ± 0.20) and EL (0.23 ± 0.04, 2.14 ± 0.16) groups, and reduced slightly in ER (1.08 ± 0.10; 3.39 ± 0.21) group. Discussion and conclusion ES and EL induce stronger hepatotoxicity than ER through oxidative stress and the Nrf2/HO-1 pathway, and the root is a better medicinal part, which provides a basis for clinical research, safe applications, and reasonable development of C. serratus.